Review paper Selectins in dermatology - Sudnik, Wiesława; Dańczak-Pazdrowska, Aleksandra; Silny, Wojciech; Jenerowicz, Dorota (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2011)
In the course of an inflammatory reaction an inflow of cells takes place to the site of inflammation. At the beginning of the process the main role is played by selectins, the group of three proteins responsible for initiation of leukocyte adhesion to endothelial cells. Selectins are present on the cell surface while serum and body fluids contain their soluble forms. In the course of several inflammatory diseases alterations in intensity of E-selectin expression or in concentration of their soluble forms were detected. We have devoted our attention to the problem of selectins in dermatology.